The Administration of the Student Care and Support System in Educational Institutions under Sam Khok District, Pathumthani Primary Educational Service Area Office 1 - ชลาลัย, พุทธรักษา; แก้วมงคล, ทรงยศ; ประวัติรุ่งเรือง, ปราศรัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) study the administration of the student support system; 2) compare teachers’ opinions classified by gender, educational level, work experience, and school size; and 3) examine guidelines for developing the student support system. The sample consisted of 146 teachers in public schools in Sam Khok District under the Pathum Thani Primary Educational Service Area Office 1. The sample size was determined using the Krejcie and Morgan (1970) table. Stratified random sampling based on school size and simple random sampling were employed. The research instruments included a questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.80 to 1.00 and a reliability coefficient of 0.94, and a semi-structured interview. Data were analyzed using frequency, percentage, mean, standard deviation, t-test, F-test, and content analysis.            The research findings were as follows: 1. The overall administration of the student support system was at the highest level. Each aspect was also at the highest level. The highest mean was found in problem prevention and resolution, followed by student referral, knowing students individually, student promotion and development, and the lowest mean was in student screening. 2. The comparison of teachers’ opinions classified by gender, educational level, work experience, and school size revealed statistically significant differences at the .05 level for gender and at the .01 level for educational level. However, no significant differences were found in terms of work experience and school size. 3. The development guidelines should emphasize systematic and continuous implementation, including improving student data systems and screening processes, clearly classifying student groups, and developing individualized support plans alongside continuous student development. These approaches are essential mechanisms for enhancing student quality and strengthening the educational system.